Analysis of Smash Ability in Volleyball Learning in Class XI A at SMAN 7 South Bengkulu Students - Yugi Stiawan; Mesterjon Mesterjon; Supriyanto Supriyanto (Sinar Sport Journal, 2021)
This research is motivated by volleyball learning in class XI A at SMAN 7 Bengkulu Selatan students, learning in volleyball skills has been running but has not received special attention, especially smash skills. This study aims to determine the level of smash ability in class XI A in students of SMAN 7 Bengkulu Selatan. This research is quantitative descriptive. The variable in this study is the ability to smash. The sample in this study was in class XI A of 20 students of SMAN 7 Bengkulu Selatan. The method used is survey analysis and data collection techniques using tests and measurements. In this study, to see the ability of smash with a smash ability test instrument. The results showed that the norm of the test data on the results of the XI A class smash ability test at SMAN 7 Bengkulu Selatan 20 participants had the highest score of 15 and the lowest score of 7, the mean value was 10.68 and the standard deviation was 1.9. Based on the results of the analysis 0 people or (0%) are in the interval class < 7 and below, 5 people or (25%) are in the interval class > 7-9, 8 people or (40%) are in the interval class > 9-11 , 6 people or (30%) were in the interval class > 11-13, 1 person or (5%) were in the interval class > 13 and above. In addition, the smash ability test norm showed 6 people were in the good category, 8 people were in the moderate category, 5 people are in the less category, 0 people are in the very less category. So overall the smash ability in class XI A at SMAN 7 Bengkulu Selatan students is in the Medium category with the average result of deep smash ability is 10.65